2014
DOI: 10.1302/2046-3758.35.2000264
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry analysis of talus bone

Abstract: ObjectiveThe main object of this study was to use a geometric morphometric approach to quantify the left-right symmetry of talus bones. MethodsAnalysis was carried out using CT scan images of 11 pairs of intact tali. Two important geometric parameters, volume and surface area, were quantified for left and right talus bones. The geometric shape variations between the right and left talus bones were also measured using deviation analysis. Furthermore, location of asymmetry in the geometric shapes were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…The high degree of symmetry is in line with earlier studies that have demonstrated a high degree of symmetry in the lower extremity (Latimer and Lowrance, 1965). Specifically for the hindfoot, a strong degree of symmetry was demonstrated for the whole talus (Islam et al, 2014), the calcaneus (Stephan et al, 2014) and tibia, fibula, talus, and calcaneus (Tümer et al, 2018). A clear cause for the asymmetry in type 12100% 80The diagonal with bold numbers represent the corresponding classifications between the two observers.…”
Section: Bilateral Symmetrysupporting
confidence: 87%
See 1 more Smart Citation
“…The high degree of symmetry is in line with earlier studies that have demonstrated a high degree of symmetry in the lower extremity (Latimer and Lowrance, 1965). Specifically for the hindfoot, a strong degree of symmetry was demonstrated for the whole talus (Islam et al, 2014), the calcaneus (Stephan et al, 2014) and tibia, fibula, talus, and calcaneus (Tümer et al, 2018). A clear cause for the asymmetry in type 12100% 80The diagonal with bold numbers represent the corresponding classifications between the two observers.…”
Section: Bilateral Symmetrysupporting
confidence: 87%
“…Despite the known variation only two studies analyzed the degree of bilateral symmetry of the facet joints: one describing the pattern of calcaneal facets (Ragab et al, 2003), and another one describing the surface area and three-dimensional (3D) orientation of the calcaneal facets (Stephan et al, 2014). In general, literature describing the bilateral symmetry of the hindfoot is scarce (Shultz and Nguyen, 2007;Islam et al, 2014;Tümer et al, 2018). This is remarkable since many surgeons use the contralateral noninjured side as reference for anatomical reduction in case of a fractured bone (Pierre et al, 2010;Dobbe et al, 2011;Young et al, 2013;Ten Berg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, surgeons assume the bilateral symmetry of the human skeletal system for surgery purposes. Also, Islam et al demonstrated the symmetric morphology of some human bones [ 21 ]. Thus, the mirror technique offers relatively accurate patient data and minimises imaging difficulties for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Islam et al conducted a study on the morphology of the right and left tali in the same living subjects using a CT database with contributions by 3D analyses [18]. They found a strong degree of symmetry between the two sides [18]. However, their measurements were derived from simulations made from CT images [18].…”
Section: Plos Onementioning
confidence: 99%
“…They found a strong degree of symmetry between the two sides [18]. However, their measurements were derived from simulations made from CT images [18]. Based on measurement of the actual talus with no need for simulation, the present study combined data collection via systematic Vernier caliper measurement of morphometric profiles and 3D scans using a 3D scanner to obtain geometric measurement parameters of the human talus.…”
Section: Plos Onementioning
confidence: 99%